Option Listing and Information Asymmetry - Hu, Jianfeng (Review of Finance, 2018)
Abstract Option listing increases informed and uninformed trading by 12.4% and 23.9%, respectively, in the USA between 2001 and 2010, hence reducing relative information risk. We establish the causal effects using control stocks with similar propensities of listing and a quasi-natural experiment using option listing standards. The benefits are more prominent for stocks with active options trading and opaque stocks. The reduction of information risk is larger for good news than bad news, and the stock price response to earnings surprise weakens after listing. The results suggest that options improve the overall market information environment beyond substitutional effects to stock trading.